2017
DOI: 10.1158/2159-8290.cd-16-1431
|View full text |Cite|
|
Sign up to set email alerts
|

An Acquired HER2 T798I Gatekeeper Mutation Induces Resistance to Neratinib in a Patient with HER2 Mutant–Driven Breast Cancer

Abstract: We report a HER2T798I gatekeeper mutation in a patient with HER2L869R-mutant breast cancer with acquired resistance to neratinib. Laboratory studies suggested that HER2L869R is a neratinib-sensitive, gain-of-function mutation that upon dimerization with mutant HER3E928G, also present in the breast cancer, amplifies HER2 signaling. The patient was treated with neratinib and exhibited a sustained partial response. Upon clinical progression, HER2T798I was detected in plasma tumor cell-free DNA. Structural modelin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 39 publications
(42 reference statements)
0
72
0
Order By: Relevance
“…1). Consistent with this, another group separately reported identification of a gatekeeper HER2 T789I mutation in a HER2-mutant patient treated with neratinib (34). Another group recently reported a case series of patients with ER + breast cancer who developed emergence of HER2 mutations after exposure to various antiestrogen therapies (14).…”
Section: Discussionmentioning
confidence: 70%
“…1). Consistent with this, another group separately reported identification of a gatekeeper HER2 T789I mutation in a HER2-mutant patient treated with neratinib (34). Another group recently reported a case series of patients with ER + breast cancer who developed emergence of HER2 mutations after exposure to various antiestrogen therapies (14).…”
Section: Discussionmentioning
confidence: 70%
“…Further, 24% of those resistance-harboring samples (91/381) had >1 alteration associated with resistance to the same therapy, suggesting independent evolution in distinct tumor lesions (20) or sequential treatment with distinct therapies targeted to the same gene. For example, one NSCLC patient had an EML4-ALK fusion (VAF of 7.1%) and ALK SNVs reported to confer resistance to crizotinib (L1196M, 2.5%), crizotinib/alectinib (I1171T, 0.1%), and crizotinib/ceritinib/alectinib (G1202R, 5% relative to the original driver alteration and many were missed by single-metastatic-site tissue biopsy but confirmed by repeat biopsy or biopsy of multiple metastases at autopsy (21,22,25).…”
Section: The Landscape Of Actionable Resistance Alterations In Cfdnamentioning
confidence: 99%
“…However, there has been no large clinical trial of afatinib or osimertinib conducted for ERBB2 mutation-positive cancers. Moreover, recent studies have also reported the emergence of ERBB2 K753E or L755S mutation after trastuzumab treatment or of ERBB2 T798I mutation after neratinib treatment, suggesting that acquired secondary mutations may be a mechanism of resistance to ERBB2-targeted inhibitors (25,26).…”
Section: Introductionmentioning
confidence: 99%